2011
DOI: 10.1002/ijc.26301
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of osteopontin in hepatocellular carcinoma: A meta‐analysis

Abstract: Osteopontin (OPN) has been implicated in tumor development and progression for several years. However, the prognostic value of OPN overexpression in patients with hepatocellular carcinoma (HCC) remains controversial. We performed a metaanalysis to assess the relationship between OPN overexpression and clinical outcome of HCC. A meta-analysis of seven studies (1,158 patients) was carried out to evaluate the association between OPN and overall survival (OS) and disease-free survival (DFS) in HCC patients. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Previous studies have shown that N status, vessel invasion and depth of invasion were associated with an unfavorable outcome in cancer patients [37][39]. In our meta-analysis, we found that in gastric cancer, HOTAIR expression was significantly associated with lymph node metastasis and vessel invasion without heterogeneity.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have shown that N status, vessel invasion and depth of invasion were associated with an unfavorable outcome in cancer patients [37][39]. In our meta-analysis, we found that in gastric cancer, HOTAIR expression was significantly associated with lymph node metastasis and vessel invasion without heterogeneity.…”
Section: Discussionsupporting
confidence: 52%
“…In gastric cancer (Tang et al 2008), a similar importance was found between osteopontin expression and clinical stages, nodal metastasis, and distant metastasis. Emerging data support a role for osteopontin as a potential prognostic factor in various human tumors, including non-small cell cancer (Rud et al 2013), hepatocellular carcinoma (Zhang et al 2012), and prostate cancer (Forootan et al 2006). However, the correlation between osteopontin expression and survival is controversial in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The quality assessment of included studies was evaluated by the modified Newcastle–Ottawa quality assessment scale for cohort studies [20,21] (see “Newcastle-Ottawa quality assessment scale” section). This scale consists of three factors: patient selection, comparability of the study groups, and assessment of outcomes.…”
Section: Methodsmentioning
confidence: 99%